Practical Audio-Visual Chinese 1 - Guo Li Tai WAN Shi Fan Da Xue Guo Yu Jiao Xue Zhong Xin (Zheng Zhong/ Tsai Fong Books;, 2008)
Practical Audio-Visual Chinese book 1 2nd Edition (Book+MP3). The series of five levels is designed for adult non-native learner. The first volume has 12 lessons of pronunciation and simple everyday dialogues using basic vocabularies. Vocabularies are in traditional Chinese and annotated with pinyin, zhuyin (BoPoMoFo) and Tongyong pinyin. In Traditional Chinese. Distributed by Tsai Fong Books, Inc.